You can’t always get as much iron as you want: how rice plants deal with excess of an essential nutrient - Wairich, Andriele; Aung, May Sann; Ricachenevsky, Felipe Klein; Masuda, Hiroshi (Frontiers in Plant Science, 2024)
Iron (Fe) is an essential nutrient to almost all organisms. However, free Fe within cells can lead to damage to macromolecules and oxidative stress, making Fe concentrations tightly controlled. In plants, Fe deficiency is a common problem, especially in well aerated, calcareous soils. Rice (Oryza sativa L.) is commonly cultivated in waterlogged soils, which are hypoxic and can cause Fe reduction from Fe 3+ to Fe 2+ , especially in low pH acidic soils, leading to high Fe availability and accumulation. Therefore, Fe excess decreased rice growth and productivity. Despite the widespread occurrence of Fe excess toxicity, we still know little about the genetic basis of how rice plants respond to Fe overload, and what are the genes involved in variation when comparing genotypes with different tolerance levels. Here we review the current knowledge about physiological and molecular data on Fe excess in rice, providing a comprehensive summary for the field.